2000
DOI: 10.7863/jum.2000.19.5.315
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal ultrasonography in children and young adults: bowel wall thickness is age dependent.

Abstract: The purpose of this study was to investigate bowel wall thickness in children, adolescents, and young adults as measured by ultrasonography. Ultrasonographic evaluation of the small bowel and the colon was performed in 128 subjects (age range, 3 days to 40 years). Bowel wall thickness increased significantly (P < 0.0001) increased with age, reaching a maximum colon wall thickness of 2.0 mm at the age range of 20 to 29 years. In the ileum, maximum wall thickness reached 1.5 mm at the age range of 10 to 14 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…Our study showed GI wall thickness results that were similar to what Haber et al [11] found in young adults and Sandek et al [16] found in a control group, but they differ from the values obtained in several other studies [13 -15, 22]. We believe the explanation for this is twofold.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Our study showed GI wall thickness results that were similar to what Haber et al [11] found in young adults and Sandek et al [16] found in a control group, but they differ from the values obtained in several other studies [13 -15, 22]. We believe the explanation for this is twofold.…”
supporting
confidence: 77%
“…The most used parameter is GI wall thickness, but a few studies discuss the variance in wall thickness with respect to location in the GI tract and demographic factors such as height, weight and age. Wall thickness seems to vary in children and young adults [11], but to our knowledge there are no publications examining the wall thickness variation in adults. The wall of the collapsed intestine is thicker than the distended wall [12], but the influence of a non-fasting state on the wall thickness is not well known.…”
mentioning
confidence: 97%
“…Therefore, for human bowel, the variation is also likely caused by variation in bowel wall thickness and constitution. Using ultrasound, a large variation in wall thickness was found between healthy subjects [7]. The mean variation in thickness of the colon ascendens is 37% [12].…”
Section: Discussionmentioning
confidence: 98%
“…The radiologists were blinded to diagnosis and all clinical information, including prior and subsequent imaging studies. The following data were recorded: presence of a normal appendix defined by a diameter measuring less than 6 mm [11], abnormal appendix [6], appendicolith, thick-walled bowel measuring greater than 2 mm [19,20], dilated bowel measuring greater than 2.5 cm [21], echogenic RLQ fat defined as an area of increased echogenicity greater than 1 cm in diameter [15], increased hepatic periportal echogenicity defined as the qualitative increased echogenicity of the portal venule walls relative to the adjacent liver parenchyma and referred to as the "starry sky" liver [22][23][24] (Fig. 1), and bladder debris (mobile or layering echogenic material within the bladder).…”
Section: Methodsmentioning
confidence: 99%